Atomic interaction of the MEAM type for the study of intermetallics in the Al–U alloy - Pascuet, M.I.; Fernández, J.R. (Journal of nuclear materials, 2015)
Interaction for both pure Al and Al–U alloys of the MEAM type are developed. The obtained Al interatomic potential assures its compatibility with the details of the framework presently adopted. The Al–U interaction fits various properties of the Al2U, Al3U and Al4U intermetallics. The potential verifies the stability of the intermetallic structures in a temperature range compatible with that observed in the phase diagram, and also takes into account the greater stability of these structures relative to others that are competitive in energy. The intermetallics are characterized by calculating elastic and thermal properties and point defect parameters. Molecular dynamics simulations show a growth of the Al3U intermetallic in the Al/U interface in agreement with experimental evidence. •Potential parameters for Al and Al–U systems are obtained.•Intermetallics are characterized by calculating elastic and thermal properties.•Point defect diffusivities are calculated for the three intermetallics.•Growth of the Al3U intermetallic is shown to occur in the Al/U interface as in the real alloy.